2016
DOI: 10.1038/srep25410
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure reverse dipping may associate with stable coronary artery disease in patients with essential hypertension: a cross-sectional study

Abstract: The dipping variations of circadian blood pressure (BP) correlate closely with target-organ damages and cardiovascular events. The aim of this study was to investigate the relationship between BP reverse dipping and the prevalence of stable coronary artery disease (sCAD) in hypertensive patients. Clinical data and the results of 24-hour ambulatory BP monitoring (ABPM) were obtained from 718 hypertensive patients (390 males, mean age 59.6 ± 13.8 years) in a single centre in Northern China. Reverse dipping patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
(53 reference statements)
1
18
0
Order By: Relevance
“…Studies have demonstrated that non or reverse dipping [18-23] and nocturnal HT [11, 12] are associated with diabetic complications and adverse cardiovascular outcomes. Fogari et al demonstrated that non-dipping was independently associated with microalbuminuria [24].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that non or reverse dipping [18-23] and nocturnal HT [11, 12] are associated with diabetic complications and adverse cardiovascular outcomes. Fogari et al demonstrated that non-dipping was independently associated with microalbuminuria [24].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective case‐control study including 189 hypertensive patients with spontaneous intracerebral hemorrhage and 182 hypertensive controls, Sun and colleagues documented that RD pattern was much more prevalent in cases (51%) than in controls (4%). The association between RD and coronary artery disease has been evaluated in a hypertensive cohort of 267 patients with and 461 patients without stable coronary artery disease . The authors reported that this abnormal BP phenotype was 1.6‐fold more prevalent in the former than in the latter group.…”
Section: Search Methodsmentioning
confidence: 99%
“…The association between RD and coronary artery disease has been evaluated in a hypertensive cohort of 267 patients with and 461 patients without stable coronary artery disease. 42 The authors reported that this abnormal BP phenotype was 1.6-fold more prevalent in the former than in the latter group. In multivariate logistic regression analysis, RD (HR,…”
Section: In the Coronary Artery Risk Development In Young Adultsmentioning
confidence: 97%
“…Although routine antihypertensive medications seem not to influence DXA‐derived body composition, some of them may alter insulin sensitivity, glucose tolerance, and lipid profiles (eg, with thiazide diuretics) or sympathetic activity (with β‐blockers and α 1 ‐blockers). Thirdly, we defined a non‐dipping blood pressure profile based solely on SBP as in some previous reports . However, other studies have used both the SBP and DBP day‐to‐night differences for defining non‐dippers .…”
Section: Discussionmentioning
confidence: 99%